The Cambodia Research Consortium: expediting research for malaria elimination with the emergency response to artemisinin resistance framework. (December 2016) - Canavati, Sara; Lawford, Harriet; Fatunmbi, Bayo; Lek, Dysoley; Leang, Rithea; Top Samphor, Narann; Dondorp, Arjen; Huy, Rekol; Kazadi, Walter
Abstract This commentary offers insight into how to best address barriers that may hinder the translation of malaria research findings into policy. It also proposes viable methods of implementing these policies in Cambodia. Currently, a wide range of malaria research is being conducted by in-country stakeholders, including Cambodia's National Programme for Parasitology, Entomology and Malaria Control's (CNM), non-governmental organizations, and academic institutions. Coordinating research amongst these partners, as well as within the Ministry of Health, is a challenge. Results are rarely disseminated widely and seldom inform programme and policy decisions. CNM and its research partners have severely limited access to each other's databases. This lack of accessibility, timeliness, engagement and cooperation between CNM and its partners greatly impacts overall research efficiency in this field, and is stifling innovation both within and beyond CNM. Cambodia has set a goal to eradicate all forms of malaria by 2030. As countries approach the elimination phase, there is a greater need for sharing research-generated evidence amongst partners, in order to ensure that appropriate and impactful activities are conducted. The Cambodian Research Consortium was established to serve as a framework for partners, stakeholders and researchers to share research projects, information and results, and to promote the goals of CNM. The sharing of malaria research results will help to inform prevention, control and elimination activities in the country. It will also determine and address the country's operational research needs, and could potentially become a framework model to be used in other countries aiming to transition from malaria control to elimination.